ANALYTIC REPRESENTATION OF A PRIMITIVE DISTRIBUTION - Rechkoski, Nikola; Rechkoski, Vasko (Matematichki Bilten, 2003)
In this work we give a theorem for analytic representation of a primitive distribution for a given distribution. We give two examples.